Clinical presentations and treatment outcomes of Hashimoto encephalopathy at Siriraj Hospital – Thailand’s largest national tertiary referral center - Chaisak Dumrikarnlert; Smathorn Thakolwiboon; Vorapun Senanarong (BMC Neurology, 2023)
Abstract Background Hashimoto encephalopathy has multiple clinical presentations, and other than the presence of thyroid antibody, laboratory and imaging investigations are all non-specific. Data specific to the clinical presentations and treatment outcomes of patients with Hashimoto encephalopathy in Thailand remain scarce. Objectives To retrospectively investigate the clinical presentations and treatment outcomes of patients with Hashimoto encephalopathy at Siriraj Hospital. Methods Patients who presented with acute encephalopathy at our center during July 2012-March 2017 were evaluated for eligibility. The inclusion criteria were positive anti-thyroperoxidase (anti-TPO) or anti-thyroglobulin (anti-Tg) in serum with negative neuronal antibody in serum or cerebral spinal fluid (CSF). Clinical presentations, symptom duration, laboratory results of thyroid status and thyroid autoantibody, CSF study, and clinical outcomes were collected. Results Of the 204 patients who presented with encephalopathy, 31 (15.2%) were positive for the anti-TPO or anti-Tg antibody. Of those, 13 patients met the diagnostic criteria for Hashimoto encephalopathy. Clinical presentations included cognitive impairment (76.9%), clouding of consciousness (46.2%), and behavior change (30.8%). The neuropsychiatric presentations were visual hallucination (30.8%), auditory hallucination (15.4%), delusion (7.7%), and mood disturbance (23.1%). Other clinical presentations included seizure (38.5%), abnormal movement (23.1%), sleep disturbance (38.5%), ataxia (46.2%), stroke-like episode (15.4%), and fever (15.4%). Most patients (76.9%) had onset within < 3 months. Regarding outcomes, 1 patient who did not receive corticosteroid died from status epilepticus and septic shock. Among the 12 patients who received corticosteroid, 9 (75%) had marked improvement, 1 (8.3%) had slight improvement, and 2 (16.6%) had no clinical improvement. Seven patients (53.9%) had normal thyroid function, 4 patients (30.8%) had subclinical hypothyroidism, and 2 patients (15.4%) had subclinical hyperthyroidism. Conclusions The results of this study revealed cognitive impairment, neuropsychiatric symptoms, seizure, ataxia, and sleep disturbance to be common manifestations of Hashimoto encephalopathy. This condition should always be considered in individuals with subacute onset of unexplained cognitive impairment or cerebellar ataxia. Laboratory and neuroimaging investigations were all found to be nonspecific in Hashimoto encephalopathy. Most patients responded well to treatment, so clinical suspicion and early diagnosis and treatment will lead to improved patient outcomes.